FIQH FOR MILITARY SERVICE: Guidance for the Muslim Minority in Australia - Hyder Gulam (Media Syari'ah, 2017)
The term ‘Muslim Minority’ is used to refer to those Muslims that form an Islamic community in countries where Muslims are neither the majority, nor form the governing polity i.e. non-Muslim lands. This paper introduces Islamic Law and Fiqh, before discussing the rights and obligations of the Muslim Minority in militar y ser vice. This paper then discusses the relevant ‘ibadah rulings (literally meaning religious rituals such as prayer, fasting) and how these may be practically applied in the context of ser vice as a loyal and effective sailor, soldier or airman. The Muslim minority and their militar y ser vice in Australia will be used throughout the paper as an illustrative case study.